(untitled) (Revista Internacional de Formação de Professores, 2023)
This study systematizes the results of participating research, conducted at Professional Master´s Degree in a university in the Brazilian state of Santa Catarina. Its purpose was to design a proposal of continued training for teachers of Middle School final grades, guided by complex thinking, by transdisciplinarity, and by eco-formation and committed to meeting the global demands and the needs presented by very participants in the study. The results indicate that the training proposal met both local and global demands, clearly demonstrating the potential of teacher education towards the metamorphosis of the pedagogical practices. It also emphasized some possibilities of being re-dimensioned as a crucial condition to de-colonize teacher training at large.